2011
DOI: 10.1007/s00595-009-4362-5
|View full text |Cite
|
Sign up to set email alerts
|

Foreign bodies in the rectum: An analysis of 30 patients

Abstract: The most common reason for a foreign body in the rectum is insertion for erotic purposes. The first target of therapy should be extraction of the foreign body using the simplest method possible. Meanwhile, protecting the integrity of the intestine is of the utmost importance. The care for maintaining the integrity of the rectum should include an evaluation of the patient's psychological status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 12 publications
0
16
0
4
Order By: Relevance
“…Stable patients with no signs of perforation or peritonitis are taken up for transanal removal 6. A non-sharp palpable object less than 10 cm from the anal verge may be considered for bedside removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable patients with no signs of perforation or peritonitis are taken up for transanal removal 6. A non-sharp palpable object less than 10 cm from the anal verge may be considered for bedside removal.…”
Section: Discussionmentioning
confidence: 99%
“…Objects with an edge are grabbed with a forceps and others are extracted with a variety of instruments depending on the object shape. For proximally located objects in stable patients, Valsalva6 Manoeuvre may be tried to push the object distally 2. Some authors have reported the use of a three-way Foley’s balloon,13 pneumatic dilatation balloon14 or endotracheal tube inflated beyond the object to apply downward traction on the object 7.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, patient has inserted the object body into own rectum; rarely it may happen accidentally, or it may be the result of a criminal act. In the present cases, both patients had inserted foreign objects into their rectum seeking sexual satisfaction [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Perforation and peritonitis can develop if no intervention occurs at this stage, which might be hazardous. 20 Digital rectal examination is very important. The goals of radiological patient assessment are to determine the type, number, size, shape, and location of the foreign body inserted into the rectum and the presence of any associated complications.…”
Section: Types Of Rectal Foreign Bodiesmentioning
confidence: 99%